Assessment of coronary stent deployment using computer enhanced x‐ray images‐validation against intravascular ultrasound and best practice recommendations. Issue 3 (19th January 2012) - Davies, Andrew G.; Conway, Dwayne; Reid, Scott; Cowen, Arnold R.; Sivananthan, Mohan
<x xml:space="preserve">Abstract</x> Objective: To investigate the accuracy of stent measurements using coronary x‐ray angiograms with a computer based stent enhancement algorithm applied (StentBoost, SB). To derive recommendations for best practice when using such systems. Background: Computer enhancement algorithms allow better visualization of intracoronary stents to assist in ensuring adequate stent deployment. Factors that affect the accuracy of measurements taken on such systems are yet to be fully understood. Methods: We analysed stent deployment of 43 stents in 33 patients measuring minimum stent diameter and cross sectional area (CSA) using intravascular ultrasound (IVUS), SB enhanced x‐ray images, and quantitative coronary angiography (QCA). We investigated if the use of two projections and method of calibration influenced correlation between IVUS and SB measurements. Results: Using two views and performing calibration via the guide catheter improved agreement between SB and IVUS measurements. For example, minimum stent diameter assessed with SB using one view and balloon markers for calibration produced a correlation coefficient, r, of 0.21, whereas using two views and the guide catheter for calibration increased agreement to r = 0.62. Relative measures of stent deployment, such as the ratio of minimum to maximum CSA, produced good correlation between IVUS and SB (r = 0.74). Conclusions: When using the SB system, two projection angles should be used to image the stent. For absolute measurements, the guide catheter should be used for calibration purposes. Relative measures of stent size, which are probably sufficient for assessment of deployment, also give good agreement with similar measures on IVUS, and require no calibration. © 2012 Wiley Periodicals, Inc.